Kulit Buah Kakao (Theobroma kakao L) sebagai Bahan Pembersih Gigi Tiruan dan Mencegah Perlekatan Candida albicanss pada Basis Plat Akrilik - Widyapramana Dwi Atmaja (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2015)
Nowadays development of natural materials as an alternative denture cleanser is being developed. The use of natural ingredients is intended to reduce costs and minimize the side effects of synthetic material. One of the natural ingredients that are developed are skin of choccolate or cocoa pod husk (Theobroma cacao L). Indonesia is the third largest producer of cocoa bean in the world. One of the residues produced after removal of the cocoa bean from the fruit is cocoa pod husk (CPH). Cleaning of denture, mechanically or chemically is the effort to prevent oral candidiasis and denture stomatitis. Denture cleaning agents with chemical solution is used to remove plaque formation, mucin, discoloration, food residue, tartar and bad breath. Cocoa skin extract 2% and 0.5% as a mouthwash can reduce the number of colonies of Streptococcus sp. Ointment 10% cocoa skin extract also has the ability to reduce colonies of Streptococcus sp in patients with aphthous stomatitis.  The objective of this study literature is to determine the ability of anti candida from cocoa pod husk as an alternative denture cleanser material. This is due to the activity of the active ingredient of cocoa flavonoids and polyphenols that are comprised of catechins.